Overcoming Career Plateau: The Role of AI in Shaping ‎Women’s Career Paths in Finance - Karademir, Metin (International Journal of Accounting and Economics Studies, 2025)
This study explores the relationship between artificial intelligence (AI) and career plateaus among women working in corporate finance roles ‎in Istanbul. Semi-structured interviews were conducted with seven professionals occupying junior, mid-level, and managerial positions. The ‎interviews focused on everyday applications of AI, including performance dashboards, promotion lists, learning recommendations, and ‎financial forecasting and reporting. Perceptions of both opportunities and challenges were examined, together with their influence on ‎feelings of career stagnation or progress. A reflexive thematic analysis was applied.‎ The findings suggest that AI helps make employee contributions more visible and supports performance discussions with shared evidence. ‎Personalized learning recommendations were described as valuable, particularly for early-career employees seeking direction. However, ‎several difficulties emerged. Some aspects of work, such as coordination, mentoring, and handling crises, were often overlooked by AI ‎metrics. The constant presence of scoring mechanisms was reported to create pressure and anxiety. In addition, decision-making processes ‎sometimes slowed down when AI outputs were mediated by unclear committee structures.‎ More positive results were observed when AI was used in an advisory role, supported by transparent human review and regular bias ‎checks. Career planning was more effective when personal circumstances such as mobility, language, and caregiving responsibilities were ‎recognized. Although based on a small and non-random sample, the study offers evidence from Istanbul and highlights pathways for ‎broader future research‎.